1965
DOI: 10.1002/aja.1001170203
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of the aglomerular nephron of the toadfish, Opsanus tau

Abstract: Kidney cell fine structure in the aglomerular fish, Opsanus tau, varies profoundly with different fixation procedures. An extensive system of cisternae, tubules and irregular-shaped elements of smooth-surfaced membranes are seen in the basal cytoplasm after fixation with 2% OsOa buffered with s-collidine. Permanganate fixation demonstrates these membranes as extensions of the basal plasmalemma. Mitochondria and homogeneous bodies surrounded by a single dense membrane lie in close association with the basal mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Previous studies of aglomerular kidneys have dealt with the histology or ultrastructure of single species or of a few unrelated species (Edwards, 1928;Grafflin, 1931Grafflin, , 1937Bulger, 1965;Olsen & Ericsson, 1968;Ericsson & Olsen, 1970). The study reported here is the first to consider the pattern of glomerular development in a large, related group of primarily aglomerular teleosts.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies of aglomerular kidneys have dealt with the histology or ultrastructure of single species or of a few unrelated species (Edwards, 1928;Grafflin, 1931Grafflin, , 1937Bulger, 1965;Olsen & Ericsson, 1968;Ericsson & Olsen, 1970). The study reported here is the first to consider the pattern of glomerular development in a large, related group of primarily aglomerular teleosts.…”
Section: Introductionmentioning
confidence: 96%
“…The structure of the kidney in most taxons of fishes has been studied in considerable detail. Data are available on the gross morphology and ultrastructure of nephrons in marine and freshwater elasmobranchs (Bargmann, 1937;Kempton, 1943Kempton, ,1962Kempton, ,1964Borghese, 1966;Ogawa & Tetsuya, 1982;Gambaryan, 1987a.b), holosteans (De Smet, 1963) and marine (Edwards, 1928;Grafflin, 1937;Bulger, 1965;Olsen, 1970;Zuasti et al, 1983), freshwater (Gritzka, 1963;Vinnichenko et al, 1975) and euryhaline (Edwards, 1935;Anderson & Loewen, 1975;Makoto & Masao, 1982) teleosts. However, the morphology of the excretory system in chondrosteans (sturgeons) has not received much attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…Aglomerular bony fish and elasmobranchs have al ready been used as models to study the func tion of the proximal tubule [1,2]. In the study presented here, the Atlantic hagfish (Myxine glutinosa) is proposed as a model to study glo merular function.…”
Section: Introductionmentioning
confidence: 99%